Nutrição pré-parto da vaca e seus reflexos na produção e composição do leite e no desempenho do bezerro - Adams, Sander Martinho (2019)
Maternal nutrition during gestation may determine progeny performance, since postnatal muscle development occurs through hypertrophy of the muscle fibers formed during fetal development. However, maternal nutrition during gestation also modifies the cow's body condition score at calving, which may influence milk production and quality and consequently the performance of the suckling calf. However, the production and nutritional value of this food usually in the studies are not considered, and the consequences of fetal programming can be overestimated the offspring's postnatal growth. Thus, the objective of this study was evaluate how nutrition in the final third of gestation influences the cow body condition score, milk production and composition on the development of the suckling calf. Fifty-four multiparous cows from the same experimental herd were distributed considering age, genetic group, weight and body condition score in three treatments according to the prepartum nutritional level: Low; Medium and High. The nutritional level was adjustment with concentrated supplementation based on corn, soybean meal and urea. Were evaluated: cow body condition score, milk yield and nutritional value, and weight performance of calves. Cows with Low nutritional level in the final third of gestation had a lower body condition score at parturition. There was no difference in the milk production, but the nutritive value of this food was higher for protein, lactose, ashes and dry stratum defatted (P <0.05) in cows from treatment High. The treatments did not influence the calf birth weight (P> 0.05), but cows submitted to Low nutritional level in the final third gestation weaned lighter calves at 176 days of age, with 179.07 kg vs. 191.44 and 185.46 kg, respectively for Medium and High level. Therefore, it is possible to maximize progeny performance until weaning through maternal nutrition in the final third of gestation, with modulation of the cow's body condition score and milk nutritional value ingested by the offspring.